Microscopic examination of normal nail clippings - Betina Werner; Andre Antunes (Mattioli1885, 2013)
Background: Nail clipping analysis for diagnosing causes of onychodystrophy other than onychomycosis is investigated to a very small extent. In order to achieve acceptance as a diagnostic method for any kind of nail abnormalities, normal microscopic parameters have to be established first. In most reported cases,  nail plates were fixed in formalin with processing of the specimens with routine automated histotechnique.